The impacts of Ramadan fasting for patients with non-alcoholic fatty liver disease (NAFLD): a systematic review - Lin, Xiaoxiao; Wu, Guomin; Huang, Jinyu (Frontiers in Nutrition, 2024)
Background Numerous studies have explored the impacts of Ramadan fasting on Non-alcoholic fatty liver disease (NAFLD). Therefore, the objective of this systematic review was to analyze and summarize all clinical studies regarding the impacts of Ramadan fasting for patients with NAFLD. Methods We performed a comprehensive search of the Embase, Cochrane, and PubMed databases from inception to September 1, 2023. All clinical studies concerning the impacts of Ramadan fasting on patients with NAFLD were included. Results In total, six studies with 397 NAFLD patients comprising five prospective studies and one retrospective study were included in the systematic review. All six studies were assessed as high-quality. Ramadan fasting may offer potential benefits for patients with NAFLD, including improvements in body weight, body composition, cardiometabolic risk factors, glucose profiles, liver parameters, and inflammation markers. Conclusion Ramadan fasting might be an effective dietary intervention for NAFLD. However, the number of studies examining the impacts of Ramadan fasting for patients with NAFLD is relatively limited. Therefore, more high-quality research is needed to further our understanding of the benefits of Ramadan fasting for NAFLD. Systematic review registration https://inplasy.com, identifier 202390102.